Socratics before Socrates - Kubok, Dariusz (Folia Philosophica, 2012)
Review of Matuš Porubjak's book: Vôl’a (k) celku. Man and Community in the Words of Homer and Theognis. Pusté Úlany: Schola Pholosophica, 2010.